City visions : imagining place, enfranchising people - Gaffikin, Frank; Morrissey, Mike, 1946- (Pluto Press, 1999)
Annotation Covering a range of North American and European cities, but focusing on Belfast's social, economic and political developments, this collection considers the role of long-term urban planning in the development of cities. The major cities of the West are characterised by division, uneven development and unequal distribution of jobs. In Belfast these general Western urban characteristics are extended and heightened by association with a long-standing political crisis and low-intensity conflict. Covering a range of North American and European cities, but focusing on Belfast's social, economic and political developments, this collection considers the role of long-term urban planning in the development of cities. The authors integrate global debates on urban development and summarise contemporary theories on cities and their future. An assortment of interventions and delivery mechanisms are considered, and among the key topics covered are urban economies and social exclusion; the planning of city regions; the sustainable city; urban regeneration; the role of culture in remaking cities; and the future governance of cities. By viewing the subject from a local perspective, as well as in an international context, the authors provide a stimulating critique which will guide policy makers, planners, students and others concerned with urban regeneration.